Cruising down millennials’ fashion runway:a cross-functional study beyond Pacific borders - Cham, Tat Huei; Cheng, Boon Liat *; Ng, Caryn Kar Yan (Emerald, 2020)
Purpose – The clothing industry is one of the earmarked industries in many countries following the rising demand and consumption of clothing products among millennials. Malaysia and Thailand are known to be promising markets for this industry in the South East Asia region. The purpose of this study is to investigate the influence of psychological and marketing factors on clothing interest among Generation Y consumers, as well as the interrelationships between self-confidence, product attitude and purchase intention. The impact of nationality was also examined as a moderator on the investigated relationships. Design/methodology/approach – The data was collected among Generation Y consumers using a survey questionnaire, which had successfully gathered a total of 388 usable cases from the capital cities of Malaysia (Kuala Lumpur) and Thailand (Bangkok). These cities were selected for being the largest cities in its country which contain the highest number of shopping malls, offices and Generation Y population. Data analysis was then performed using both the SPSS andAMOS software. Findings – Findings obtained acknowledged the importance of both psychological (i.e. fashion innovativeness, self-concept, fashion consciousness and need for uniqueness) and marketing (i.e. social media marketing and fashion advertisement) factors towards the clothing interest among Generation Y consumers. Consequently, clothing interest would influence their product attitude, self-confidence and purchase intention, with product attitude and self-confidence as the mediators between clothing interest and purchase intention. Multigroup analysis confirmed that there are differences between Generation Y consumers in both Malaysia and Thailand, where Thai consumers hold a stricter emphasis concerning the influence of social media marketing on clothing interest and self-confidence on purchase intention. Originality/value – This study is one of the very few studies that explored the minimally investigated territory on the consequential importance of clothing interest within the clothing industry, specifically, through extending the literature on the influence of psychological and marketing factors towards the individuals’ clothing interest. Moreover, this study also successfully highlighted the mediation role of product attitude and self-confidence in the relationship between clothing interest and purchase intention.